Rapid short-pulses of focused ultrasound and microbubbles deliver a range of agent sizes to the brain - William Lim Kee Chang; Tiffany G. Chan; Federica Raguseo; Aishwarya Mishra; Dani Chattenton; Rafael T. M. de Rosales; Nicholas J. Long; Sophie V. Morse (Scientific Reports, 2023)
Abstract Focused ultrasound and microbubbles can non-invasively and locally deliver therapeutics and imaging agents across the blood–brain barrier. Uniform treatment and minimal adverse bioeffects are critical to achieve reliable doses and enable safe routine use of this technique. Towards these aims, we have previously designed a rapid short-pulse ultrasound sequence and used it to deliver a 3 kDa model agent to mouse brains. We observed a homogeneous distribution in delivery and blood–brain barrier closing within 10 min. However, many therapeutics and imaging agents are larger than 3 kDa, such as antibody fragments and antisense oligonucleotides. Here, we evaluate the feasibility of using rapid short-pulses to deliver higher-molecular-weight model agents. 3, 10 and 70 kDa dextrans were successfully delivered to mouse brains, with decreasing doses and more heterogeneous distributions with increasing agent size. Minimal extravasation of endogenous albumin (66.5 kDa) was observed, while immunoglobulin (~ 150 kDa) and PEGylated liposomes (97.9 nm) were not detected. This study indicates that rapid short-pulses are versatile and, at an acoustic pressure of 0.35 MPa, can deliver therapeutics and imaging agents of sizes up to a hydrodynamic diameter between 8 nm (70 kDa dextran) and 11 nm (immunoglobulin). Increasing the acoustic pressure can extend the use of rapid short-pulses to deliver agents beyond this threshold, with little compromise on safety. This study demonstrates the potential for deliveries of higher-molecular-weight therapeutics and imaging agents using rapid short-pulses.